Study the IL-12/P70 serum level in acute myeloid leukemia patients before &after chemotherapy - et.al, T.A_A. Hussain (Al-Qadisiyah Journal of Pure Science, 2017)
IL-12 P70 is a key immunoregulatory cytokine with a molecular weight of 70 kDa . is produced mainly by DCs, MÐ¤s, monocytes, neutrophils, microglia cells and, to a lesser extent, by B cells IL-12 exerts potent anti-tumor activity through activation of immune effector mechanisms or direct targeting of tumor cells. The aim of this study to evaluate serum IL-12 P70 concentration of patients before and after treatment ,and comparative with control subjects . The other aims is to associate this protein with age groups stage and the gender . A direct ELISA was used to quantify serum IL-12 P70 concentrations in 60 patients with acute myeloid leukemia (AML)and 15 healthy subjects (control) . We found serum concentrations of IL-12 P70 were significant increase in patients with AML after treatment in compared with patients before treatment (P< 0.5) . Experimental data suggest that they may suppress apoptosis and thus promote tumorigenesis